2012
DOI: 10.4028/www.scientific.net/ast.86.22
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Synthesis and Characterization of Lanthanide-Substituted Nanostructured Calcium Hydroxyapatite

Abstract: In this study, nanostructured Ce- and Sm-substituted Ca10(PO4)6(OH)2 samples have been synthesized using an aqueous sol-gel chemistry route. For the characterization of obtained specimens, the XRD, SEM, UV-visible reflection and IR spectroscopy and luminescence measurements were recorded. It was shown that phase purity of the end products highly depends on the amount of lanthanide element. The reflectance of lanthanide-substituted calcium hydroxyapatite samples is wavelength independent in the wavelength range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Incorporated Ln 3+ in the HA matrix include (La 3+ ), [19][20][21] (Y 3+ ) and (In 3+ ), 19 (Sm 3+ ) and (Gd 3+ ) 22 and, also, in nanostructured HA, namely (Ce 3+ ) 23 and (Ce 3+ & Sm 3+ ). 24 HA and TCP lanthanum phosphate composites have also been reported. 25 An important feature of lanthanides is their apparent antimicrobial properties.…”
Section: Introductionmentioning
confidence: 98%
“…Incorporated Ln 3+ in the HA matrix include (La 3+ ), [19][20][21] (Y 3+ ) and (In 3+ ), 19 (Sm 3+ ) and (Gd 3+ ) 22 and, also, in nanostructured HA, namely (Ce 3+ ) 23 and (Ce 3+ & Sm 3+ ). 24 HA and TCP lanthanum phosphate composites have also been reported. 25 An important feature of lanthanides is their apparent antimicrobial properties.…”
Section: Introductionmentioning
confidence: 98%
“…Metal-substituted Ca 10 (PO 4 ) 6 (OH) 2 nanocrystallites were also synthesized by an aqueous sol-gel synthesis routes [135,136,144,146,151,154,158,160,163,164,166,168,170,172,[174][175][176]. In most of the cases cationic substitution of calcium did not changed the surface morphology of the end product.…”
Section: Introductionmentioning
confidence: 99%
“…It was also suggested that transition metals and lanthanide elements might play an important role in enamel demineralization reduction [15,16]. Apatites with the chemical formula Sr 7-x Ca x La 3 (PO 4 ) 3 (SiO 4 ) 3 F 2 , where x = 0, 1 and 2, were prepared by mechanochemical synthesis using a planetary mill [17].…”
Section: Introductionmentioning
confidence: 99%